Variaçãos sazonal e migração vertical da comunidade zooplanctônica (exceto Rotifera) do reservatório de Itupararanga, Votorantim, SP - Giron, Aline Karen Santana (2013)
The present study aimed to analyse the Itupararanga reservoir zooplankton community in relation to diel and seasonal variation and vertical migration of the organisms in the water column and verify if there are patterns of variation. For this two samples were performed in the reservoir in 2011: in February, rainy period and in july, dry period. The collections were performed in diel cycle (every four hours), in three different layers of the water column (surface, middle and bottom) and in two environments of the reservoir (dam and central body). Stratification in the water column was observed for both environments and both periods. 25 species of the mesozooplankton were identified. Chaoborus larvae were more abundant in February in relation to july and the opposite was observed for cladocerans and copepods. Among the copepods, dominance of juvenile stages (nauplii and copepodites) was observed in both environments and periods. Among the adults of copepods the specie more abundant was Notodiaptomus deitersi (1.298 org.m3) and among the cladocerans was Bosmina freyi (32.282 org.m3). The peak of the total density of the zooplankton community occurred during the dry period in the dam environment with 81.211 org.m3. Chaoborus exercised predation pressure on microcrustaceans during the rainy period. During the dry period, in the absence of Chaoborus in the water column, cladocerans and copepods were more ecologically successful. For all of the groups was observed the usual pattern of vertical migration; reverse migration was not observed. Despite predation pressure, the microcrustaceans not altered their vertical distribution for decrease special overlap with Chaoborus. For all of the groups the migration pattern adopted seems a result of escape from predators and search for good food resources.